Little Ones Listen to God - Martha Hook; Tinka Boren (USA Zondervan Publishing House, 1981)
Sixteen Old and New Testament stories retold for young children. Includes scriptural references and discussion questions.
[127] p. col. illus.
Keywords: Theology: Miscellaneous (3GddGghJ(B: (3eJaQbGJs; Bible stories, English; Theology; Bible stories